Genomic background of the Klebsiella pneumoniae NDM-1 outbreak in Poland, 2012–18. (13th August 2020) - Izdebski, R; Sitkiewicz, M; Urbanowicz, P; Krawczyk, M; Brisse, S; Gniadkowski, M
Abstract: Objectives: To characterize genomes of Klebsiella pneumoniae ST11 NDM-1 responsible for a countrywide outbreak in Poland and compare them phylogenetically with other Polish and international ST11 strains. Methods: Seventy-one carbapenemase-producing K. pneumoniae ST11 isolates from Poland, including 66 representatives of the NDM-1 epidemic from 2012–18, were sequenced using Illumina MiSeq. Additionally, three outbreak isolates were also sequenced using MinION. The clonality and phylogenetic analysis was done by core-genome MLST and SNP approaches. Resistomes, virulomes, K/O antigens and plasmid replicons were screened for. The detailed plasmid analysis was based on full assemblies using Oxford Nanopore Technologies data. Results: Chromosomes of the outbreak isolates formed an essentially homogeneous cluster (though accumulating SNPs gradually with time), differing remarkably from other Polish NDM-1/-5-, KPC-2- or OXA-48-producing K. pneumoniae ST11 strains. The cluster belonged to a clade with 72 additional isolates identified worldwide, including closely related NDM-1 producers from several countries, including organisms from Bulgaria and Greece. All these had KL24 and O2v1 antigens and the chromosomal yersiniabactin locus YbST230 residing in the ICE Kp11 element. The specific bla NDM-1 -carrying Tn 125 transposon derivative, named Tn 125 A, was located in IncFII/pKPX-1- and/or IncR-like plasmids; however, the IncRs rearranged extensively during the outbreak, contributing to highly dynamic plasmid profiles and resistomes. Conclusions: The K. pneumoniae ST11 NDM-1 genotype that has been expanding in Poland since 2012 is largely monoclonal and represents a novel international high-risk lineage that is also spreading in other countries.